QLfANTITAIVE ECOLOGY OF PHYTOPLANKTON IN THE COCHIN BACKWATER - Gopinathan, C P; Nair, P V Ramachandran; Nair, A K Kesavan (Indian Journal of Fisheries, 2011)
A one-year study on the standing crop in terms of chlorophylls, primary production and total-cell counts of four station grids has shown that there were regional and seasonal variations in the magnitude of phytoplankton production in the Cochin backwater. Statistically treated using a microcomputor, a multiple regression relationship has been established between parameters within stations. But th<^ Correlation coefBclent and Standard Regression coefficient have revealed that the plankton production and the related parameters at all the stations were independent of each other and the parameters varied from station to station. Probable reasons are briefly discussed